FUNDING AND PRIORITIES: PUBLIC LIBRARIES - FUNDING AND PRIORITIES: PUBLIC LIBRARIES - McKendrick, Joseph (Unisphere Research, 2011)
Public libraries—which rely on funding from cash-strapped local municipalities or counties—have been particularly susceptible to the recent economic downturn. Many have been forced to cut offerings and freeze staff salaries while others have turned to alternative sources of funding such as grants and fundraisers to avoid severely cutting services. Looking forward, however, fewer libraries anticipate that they will be facing cutbacks in 2011. Indeed, many libraries are coming through the crunch with much of their budgets intact and are even ramping up spending on technological and digital solutions to deliver information and services as part of a longer-term realignment with the needs of their constituents. These are just some of the conclusions of a recent survey of 490 public library managers and professionals from across North America. This study, conducted by the Library Resource Guide (LRG)—in conjunction with Unisphere Research, the market research division of Information Today, Inc. (ITI)—in October and November 2010 among libraries listed in ITI’s American Library Directory, reveals current spending patterns for public, academic, government, and special libraries and projects budget and other spending trends for 2011. A total of 1,201 libraries representing four key segments—public libraries, academic libraries, special and corporate libraries, and government (mainly state, federal and armed forces) libraries responded to the survey. Among the 490 respondents from public libraries are directors, administrators, managers, department heads, and librarians from the complete range of library settings and sizes. Just under one-fourth serve populations of fewer than 10,000 constituents, and another 18% serve between 10,000 and 50,000 people. More than one-fourth service more than 100,000 people. (For detailed demographic breakdowns, see Figures 29-32 at the end of this report.) Key findings from the survey include the following: While the past year has been difficult for many public libraries in terms of budget cuts, prospects are brighter for the year ahead. Larger public libraries suffered the most severe cuts while fewer cuts are seen among the smallest libraries, which already operate on relatively little funding. Typical annual budgets currently fall in the range of $200,000 at the extreme low end to close to $3 million, and a majority of that funding goes to staffing. Three out of four public libraries had to cut back in areas over the past year, and in most cases, this involved salary freezes for staff—particularly at larger libraries. More hardhit public library segments show a greater tendency to move away from print and to digitizing their collections and offerings. Four out of 10 public libraries have also increased efforts to solicit grants and private donations. Public libraries report a significant surge in patron demand for digital information and technology resources. There has also been a surge in demand for job search and career information, suggesting a significant role for public libraries at a time of profound economic shifts. Demand remains just as high for print materials as digital content at this time. There is also high demand for both ebooks and audiobooks. Public libraries have experienced a period of painful cuts, including online subscriptions. Public libraries are also extremely cautious when it comes to cloud computing. But there was little let-up in investments in technology hardware and software. Libraries serving mid-size communities are the most aggressive buyers of technology products. Most public libraries serving large to mid-size populations have strategic plans, and customer service tops the list of priorities going forward. Technology also is seen as a leading initiative for the public library of the 2010s. “Funding and relevancy” are key issues, according to the department head of a Southeastern public library. “While the need for the existence of the library institution is being challenged, the fact is that a large majority of the population still remains 5–10 years or more behind the technology in regards to training and being able to comfortably utilize the range of technology available. The need for digital transliteracy is becoming more apparent with the high unemployment and upcoming career opportunities. Libraries are [in a] position to meet that need and others.” Still, survey respondents were also keenly aware of the need to not only keep pace with technology and operate like a business, but also clearly communicate the value of libraries to their constituents. Community support and involvement is a bedrock practice that is vital as libraries enter the digital age. As expressed by the administrator of a Midwestern public library, “The biggest challenge facing libraries nationwide is to continue to grow services to meet the needs of the community through digital collections, computer access and social networking; and also advocating the role public libraries play in their communities to ensure that adequate funding is received and excellent services are provided.”
Funding and Priorities: The Library Resource Guide Benchmark Study on 2011 Library Spending Plans was produced by Unisphere Research and sponsored by ProQuest. Unisphere Research is the market research unit of Unisphere Media, a division of Information Today, Inc., publishers of Database Trends and Applications magazine and the 5 Minute Briefing newsletters. Unisphere Media, 229 Main Street, Chatham, NJ 07928. Tel: 973-665-1120, Fax: 973-665-1124, Email: Tom@dbta.com, Web: www.dbta.com. Data collection and analysis performed with SurveyMethods. © Copyright 2011, Information Today, Inc. All rights reserved.
Keywords: Public Libraries; Funding; Electronic Resources; Budgets and Funding